PHARMACOKINETIC RESEARCHES AND PRACTICAL MEDICINE - V. G. Belolipetskaya; Y. V. Sukhanov (Столичная издательская компания, 2015)
An article gives in a comprehensive manner the main idea of pharmacokinetics, as the science about rules of substances behavior in the internal environment of the organism, as well as of main parameters of pharmacokinetic researches. The article provides vivid and very  persuasive examples of high practical importance of this science both for creating new medical forms of drugs and for choosing the optimal of therapy regime.